Concentration of transforming growth factor beta in human bone tissue: relationship to age, menopause, bone turnover, and bone volume - Pfeilschifter, Johannes; Diel, Ingo J.; Scheppach, Beate; Bretz, Anette; Krempien, Robert; Erdmann, Johannes; Schmid-Bindert, Gerald; Reske, Nicole; Bismar, Hanadi; Seck, Thomas; Krempien, Burkhard; Ziegler, Reinhard (Journal of bone and mineral research, 1998)
Transforming growth factor β (TGF‐β) is thought to play an important role in bone metabolism, but its relationship to human bone turnover and bone mass has not been examined yet. In this study, we measured the concentration of TGF‐β in 811 samples of male and female bone from four representative sites of the human skeleton and in the supernatants of 72 short‐term human bone marrow cultures from the iliac crest. The concentrations of TGF‐β1 and TGF‐β2 in the bone matrix were positively correlated with histomorphometric indices of bone resorption and bone formation and with serum levels of osteocalcin and bone‐specific alkaline phosphatase. We also observed a positive association between the release of TGF‐β in the bone marrow cultures and serum osteocalcin. Changes in the rate of cancellous or cortical bone remodeling with age or menopause were accompanied by corresponding changes in skeletal TGF‐β. In contrast, there was no significant relationship between the concentration of TGF‐β and bone volume at any skeletal site. In conclusion, our study supports the hypothesis that TGF‐β plays an important role in human bone remodeling, but fails to demonstrate an association between the skeletal concentration of TGF‐β and human bone mass.